Progressive Development of Cefiderocol Resistance in Escherichia coli During Therapy is Associated With an Increase in blaNDM-5 Copy Number and Gene Expression. (7th October 2021) - Simner, Patricia J; Mostafa, Heba H; Bergman, Yehudit; Ante, Michael; Tekle, Tsigereda; Adebayo, Ayomikun; Beisken, Stephan; Dzintars, Kathryn; Tamma, Pranita D
Abstract: Background: As cefiderocol is increasingly being prescribed in clinical practice, it is critical that we understand key mechanisms contributing to acquired resistance to this agent. Methods: We describe a patient with acute lymphoblastic leukemia and a New Delhi metallo-ß-lactamase (NDM)–5–producing Escherichia coli intra-abdominal infection in whom resistance to cefiderocol evolved approximately 2 weeks after the start of treatment. Through whole-genome sequencing (WGS), messenger RNA expression studies, and ethylenediaminetetraacetic acid inhibition analysis, we investigated the role of increased NDM-5 production and genetic mutations contributing to the development of cefiderocol resistance, using 5 sequential clinical E. coli isolates obtained from the patient. Results: In all 5 isolates, bla NDM-5 genes were identified. The minimum inhibitory concentrations for cefiderocol were 2, 4, and >32 μg/mL for isolates 1–2, 3, and 4–5, respectively. WGS showed that isolates 1–3 contained a single copy of the bla NDM-5 gene, whereas isolates 4 and 5 had 5 and 10 copies of the bla NDM-5 gene, respectively, on an IncFIA/FIB/IncFII plasmid. These findings were correlated with those of bla NDM-5 messenger RNA expression analysis, in which isolates 4 and 5 expressed bla NDM-5 1.7- and 2.8-fold, respectively, compared to, isolate 1. Synergy testing with the combination of ceftazidime-avibactam and aztreonam demonstrated expansion of the zone of inhibition between the disks for all isolates. The patient was successfully treated with this combination and remained infection free 1 year later. Conclusions: The findings in our patient suggest that increased copy numbers of bla NDM genes through translocation events are used by Enterobacterales to evade cefiderocol-mediated cell death. The frequency of increased bla NDM-5 expression in contributing to cefiderocol resistance needs investigation. Abstract : In a patient infected with a New Delhi metallo-ß-lactamase–producing Escherichia coli isolate, whole-genome sequencing, messenger RNA expression studies, and ethylenediaminetetraacetic acid inhibition work uncovered the mechanisms that led to relatively rapid development of cefiderocol resistance.